Party princess - Cabot, Meg (New York, NY HarperCollins, 2006)
In a series of humorous diary entries, fifteen-year-old Mia tries to figure out how to raise money for the bankrupt student government at her school while also worrying about how to become a "party girl."
1
NEW, LITERATURE
Keywords: Diaries -- Fiction; High schools -- Fiction; Humorous stories; Parties -- Fiction; Princesses -- Fiction; Schools -- Fiction; Student government -- Fiction